Highly active aluminium catalysts for room temperature ring-opening polymerisation of rac-lactide - Gesslbauer,S; Cheek,H; White,A; Romain,CRE (Dalton Transactions, 2018)
A new series of aluminium complexes bearing ‘catam’ ligands has been synthesised and fully characterised. They were found to exhibit high activity at room temperature for rac-lactide ring-opening polymerisation, a rather rare feature for aluminium-based catalysts.